MEDIA INTERAKTIF SEBAGAI EDUKASI VISUAL UNTUK MENINGKATKAN KESADARAN ISU PEOPLE PLEASER PADA MAHASISWA JAKARTA: INTERACTIVE MEDIA AS A VISUAL EDUCATIONAL TOOL TO RAISE AWARENESS OF PEOPLE-PLEASER ISSUES AMONG UNIVERSITY STUDENTS IN JAKARTA - Cavin Joo Dauneeaaron; Sangayu Ketut Laksemi Nilotama; Agung Eko Budiwaspada (Universitas Trisakti, 2025)
Interactive Media as a Visual Educational Tool to Raise Awareness of People-Pleaser Issues Among University Students in Jakarta. People pleaser behavior refers to an individual's tendency to prioritize others' needs over their own in order to gain social acceptance. This pattern often appears unconsciously among university students, particularly those in the process of identity formation and seeking social belonging. The lack of awareness regarding the psychological impact of this behavior highlights the need for an educational communication strategy that resonates with youth. This study aims to design a social campaign using interactive visual media to increase student understanding of the people pleaser issue. The research adopts the Design Thinking approach, comprising five key stages: problem identification, definition, ideation, prototyping, and testing. A survey conducted among students in Jakarta revealed that most respondents were unfamiliar with the term, yet exhibited common characteristics of the behavior. Based on these findings, a campaign titled NoThanks was developed in the form of a short educational video and talk show, distributed via Instagram and YouTube. The campaign is designed to deliver information in a reflective, emotionally engaging way. Through this visual and communicative approach, the campaign aims to foster greater awareness and encourage students to establish healthier personal boundaries in their everyday social interactions.